A 15 mV-input and 71%-efficiency boost converter with 22 mV output ripple for thermoelectric energy harvesting application. (March 2022) - Lin, Yihan; Wu, Tianxian; Zeng, Yanhan; Yang, Jingci; Chen, Weijian; Li, Zhixian
Abstract: This paper presents a self-startup and ultra-low-voltage boost DC–DC converter for the thermoelectric energy harvesting application. A two-stage auxiliary boost startup circuit with a multi-stage voltage multiplier and a large duty cycle circuit is adopted to achieve a minimum self-startup voltage of 155 mV. And the system can sustain the operation at a 15 mV input. The maximum power point tracking (MPPT) with a combination of coarse and fine frequency tuning is proposed to improve the tracking accuracy with small output ripples of 22 mV. Moreover, the zero current switching (ZCS) scheme combined with the MPPT achieves a peak end-to-end efficiency of 71%, providing a regulated 1.25V output with a maximum power of 540 μ W. Highlights: A boost DC–DC converter with a 155mV self-startup achieves a 15-mV operating. The maximum power point tracking (MPPT) achieves a small 22-mV output ripple. The accurate MPPT with coarse and fine frequency tuning improves tracking accuracy. The zero current switching (ZCS) scheme obtains DCM and prevent the reverse current. The ZCS and MPPT obtains 71% efficiency, a regulated 1.25-V output and 540 μ W power.